Application of alternative treatments to control postharvest fungal infection and shelf life extension of papaya in different maturity stages (Progressive Agriculture, 2020)
An experiment was conducted to study the application of alternative treatments to control postharvest fungal infection and shelf life extension of papaya under different maturity stages at the Laboratories of the Department of Horticulture and Agricultural Chemistry, Bangladesh Agricultural University, Mymensingh during the period from August to October, 2018. The two factor experiment (maturity stages and postharvest treatments) was laid out in a completely randomized design (CRD) with three replications. Four postharvest treatments viz., control, hot water treatment (Fruits treated at 50±2ºC for 10 minutes), chitosan coating (2000ppm chitosan solution) and hot water+chitosan coating were assigned to papaya fruits which were maturity stage I or maturity stage II. Significant variations were observed between maturity stage I (green mature) and maturity stage II (0-10% yellowing of fruits) in relation to most of the parameters studied. Results showed that most of the parameters studied were significantly influenced by the afore-mentioned factors. Longer shelf life (12.64 days) was observed in maturity stage I fruits than maturity stage II fruits (12.18 days). Significant reduction in disease incidence and severity was noticed in the maturity stage I fruits as compared to maturity stage II fruits. The longest shelf life (15.20 days) was found in hot water treated and chitosan coated fruits of maturity stage I, whereas the shortest shelf life (8.52 days) was observed in control of maturity stage II fruits.Progressive Agriculture 30 (3): 298-304, 2019